Analisis Korelasi Jumlah Trombosit dengan Nilai Mean Platelet Volume to Platelet Count Ratio (MPR) pada Pasien Covid-19 - Putu Ristyaning Ayu; Ridha Riano Fathunnisa (CV. Jasa Sukses Abadi, 2023)
Coronavirus disease 2019 (Covid-19) is an infectious disease caused by SARS-CoV-2. The number of Covid-19 cases in Indonesia until November 2022 reached 6.7 million confirmed cases of Covid-19 and 160 thousand of them died. In treating Covid-19 patients quickly and accurately and reducing mortality from Covid-19, biomarkers are needed to predict patient mortality. Platelets, Mean Platelet Volume (MPV) and Mean Platelet Volume-To-Platelet Ratio (MPR) have been studied extensively and are thought to be used as predictors of the severity of Covid-19 patients. The design of this study was an observational analytic study with a cross-sectional approach which was carried out on 60 confirmed Covid-19 patients for the January-December 2021 period at Bandar Negara Husada Hospital. Based on the statistical analysis, the average platelet count was 260.5 and the MPR value was 0.04, and the results of the Pearson bivariate correlation analysis obtained r = 0.850 and p = 0.005. This study showed that there is a relationship between platelet count and MPR as a predictor of mortality and there is a difference between platelet count and MPR values in Covid-19 patients.